An evaluation of wireless real-time data of solar tracking system - Md Yusop, Azdiana; Nazrin, Mohamad Nazrul; Mohd Jahari @ Mohd Johari, Ahmad Nizam; Sulaiman, Noor Asyikin; Khamil, Khairun Nisa; Mohammed, Ramizi; Mohd Sultan, Juwita (Wydawnictwo SIGMA-NOT, 2023)
Sunlight and heat use various continually changing techniques, including solar thermal and artificial photosynthesis. These mechanisms change their orientation throughout the day as the sun maximizes energy absorption. Solar panels are directed towards the sun by the trackers that can increase solar energy compared to the fixed-angle system. Modification efficiency is improved in any solar system when the tracking system is continuously adjusted to the most favorable angle as the sun crosses the sky. The project presents the development of a solar tracking system using Arduino-UNO that allows the panel to move towards high-intensity sunlight via two LDRs. The monitoring system is implemented to record the data of solar energy parameters and factors affecting its deficiencies using ThingSpeak platform. The result shows the tracking system has efficiencies of 54.74% higher than a fixed system. The monitoring system is practical for analyzing the real-time solar panel competent environmental factors.